The Double Eagle Club's First 50 Years - Eddy LaDue; Brent Gloy (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2008)
The Double Eagle Club was established as an investment club in 1958. During that year the background work for development of the club was completed and the first investments made. The Articles of agreement indicate that the purpose of the Club is to (1) Educate members in principles and techniques of investment, and (2) Enable members to invest funds mutually. Membership is limited to Cornell Agricultural Economics Professional Staff Members with a minimum appointment of three years.
Keywords: 330